Adaptive management: where are we now? - Rist, Lucy; Campbell, Bruce M.; Frost, Peter (Environmental Conservation, 2013)
Adaptive management (AM) emerged in the literature in the mid-1970s in response both to a realization of the extent of uncertainty involved in management, and a frustration with attempts to use modelling to integrate knowledge and make predictions. The term has since become increasingly widely used in scientific articles, policy documents and management plans, but both understanding and application of the concept is mixed. This paper reviews recent literature from conservation and natural resource management journals to assess diversity in how the term is used, highlight ambiguities and consider how the concept might be further assessed. AM is currently being used to describe many different management contexts, scales and locations. Few authors define the term explicitly or describe how it offers a means to improve management outcomes in their specific management context. Many do not adhere to the idea as it was originally conceived, despite citing seminal work. Significant confusion exists over the distinction between active and passive approaches. Over half of the studies reporting to implement AM claimed to have done so successfully, yet none quantified specific benefits, or costs, in relation to possible alternatives. Similarly those studies reporting to assess the approach did so only in relation to specific models and their parameterizations; none assessed the benefits or costs of AM in the field. AM is regarded by some as an effective and well-established framework to support the management of natural resources, yet by others as a concept difficult to realize and fraught with implementation challenges; neither of these observations is wholly accurate. From a scientific and technical perspective many practical questions remain; in particular real-world assessments of the value of experimentation within a management framework, as well as of identified challenges and pathologies, are needed. Further discussion and systematic assessment of the approach is required, together with greater attention to its definition and description, enabling the assessment of new approaches to managing uncertainty, and AM itself.
Keywords: Adaptive Management; Decision making; Natural resource management; conservation; experimental management; uncertainty

Technical challenges in the application of adaptive management - Williams, Byron K.; Brown, Eleanor D. (Biological Conservation, 2016)
Adaptive management is an approach for simultaneously managing and learning about natural resources, by acknowledging uncertainty and seeking to reduce it through the process of management itself. Adaptive decision making can be applied to pressing issues in conservation biology such as species reintroduction, disease and invasive species control, and habitat restoration, as well as to management of natural resources in general. After briefly outlining a framework and process for adaptive management, we focus on an overview of the key technical issues related to problem framing and the ability of resource managers to learn from their experience. These technical issues include the treatment of uncertainty and its propagation over time; nonstationarity in long-term environmental trends; the applicability of adaptive management across scales; requirements for models and management alternatives that promote learning; the value of the information produced with adaptive management; the challenge to management of uncertainty and surprise; and institutional (social) learning. To accommodate these and other challenges that are now coming into focus, the learning-based approach of adaptive management will need to be adjusted and expanded in the future.
Keywords: Adaptive Management; Learning; Nonstationarity; Resilience; Uncertainty; Value of information

Adaptive management of natural resources—framework and issues - Williams, Byron K. (Journal of Environmental Management, 2011)
Adaptive management, an approach for simultaneously managing and learning about natural resources, has been around for several decades. Interest in adaptive decision making has grown steadily over that time, and by now many in natural resources conservation claim that adaptive management is the approach they use in meeting their resource management responsibilities. Yet there remains considerable ambiguity about what adaptive management actually is, and how it is to be implemented by practitioners. The objective of this paper is to present a framework and conditions for adaptive decision making, and discuss some important challenges in its application. Adaptive management is described as a two-phase process of deliberative and iterative phases, which are implemented sequentially over the timeframe of an application. Key elements, processes, and issues in adaptive decision making are highlighted in terms of this framework. Special emphasis is given to the question of geographic scale, the difﬁculties presented by non-stationarity, and organizational challenges in implementing adaptive management.

Improving our legacy: Incorporation of adaptive management into state wildlife action plans - Fontaine, Joseph J. (Journal of Environmental Management, 2011)
The loss of biodiversity is a mounting concern, but despite numerous attempts there are few large scale conservation efforts that have proven successful in reversing current declines. Given the challenge of biodiversity conservation, there is a need to develop strategic conservation plans that address species declines even with the inherent uncertainty in managing multiple species in complex environments. In 2002, the State Wildlife Grant program was initiated to fulﬁll this need, and while not explicitly outlined by Congress follows the fundamental premise of adaptive management, ‘Learning by doing’. When action is necessary, but basic biological information and an understanding of appropriate management strategies are lacking, adaptive management enables managers to be proactive in spite of uncertainty. However, regardless of the strengths of adaptive management, the development of an effective adaptive management framework is challenging. In a review of 53 State Wildlife Action Plans, I found a keen awareness by planners that adaptive management was an effective method for addressing biodiversity conservation, but the development and incorporation of explicit adaptive management approaches within each plan remained elusive. Only w25% of the plans included a framework for how adaptive management would be implemented at the project level within their state. There was, however, considerable support across plans for further development and implementation of adaptive management. By furthering the incorporation of adaptive management principles in conservation plans and explicitly outlining the decision making process, states will be poised to meet the pending challenges to biodiversity conservation.

Passive and active adaptive management: Approaches and an example - Williams, Byron (Journal of Environmental Management, 2010)
Adaptive management is a framework for resource conservation that promotes iterative learning-based decision making. Yet there remains considerable confusion about what adaptive management entails, and how to actually make resource decisions adaptively. A key but somewhat ambiguous distinction in adaptive management is between active and passive forms of adaptive decision making. The objective of this paper is to illustrate some approaches to active and passive adaptive management with a simple example involving the drawdown of water impoundments on a wildlife refuge. The approaches are illustrated for the drawdown example, and contrasted in terms of objectives, costs, and potential learning rates. Some key challenges to the actual practice of AM are discussed, and tradeoffs between implementation costs and long-term benefits are highlighted.

An Introduction to Adaptive Management for Threatened and Endangered Species - Runge, Michael C. (Journal of Fish and Wildlife Management, 2011)
Management of threatened and endangered species would seem to be a perfect context for adaptive management. Many of the decisions are recurrent and plagued by uncertainty, exactly the conditions that warrant an adaptive approach. But although the potential of adaptive management in these settings has been extolled, there are limited applications in practice. The impediments to practical implementation are manifold and include semantic confusion, institutional inertia, misperceptions about the suitability and utility, and a lack of guiding examples. In this special section of the Journal of Fish and Wildlife Management, we hope to reinvigorate the appropriate application of adaptive management for threatened and endangered species by framing such management in a decision-analytical context, clarifying misperceptions, classifying the types of decisions that might be amenable to an adaptive approach, and providing three fully developed case studies. In this overview paper, I define terms, review the past application of adaptive management, challenge perceived hurdles, and set the stage for the case studies which follow.

Principles for Monitoring, Evaluation, and Adaptive Management of Environmental Water Regimes - Webb, J. Angus; Watts, Robyn J.; Allan, Catherine; Warner, Andrew T. (Water for the Environment, 2017)
Environmental water is often a contentious investment in the environment that must be delivered under uncertainty regarding the ecological and social benefits they deliver. Adaptive management can be used to facilitate decision making under uncertainty, and use new knowledge and understanding to improve management decisions and outcomes over time. However, there is a perception that adaptive management has failed to deliver improvements in decision making and learning. Monitoring and evaluation are an essential feature of adaptive management. However, past monitoring for river protection and restoration has too often been of insufficient quality to facilitate adaptive learning. Moreover, environmental water represents a class of protection and restoration that is inherently difficult to monitor, and some of the learnings are not evident in part because fragmented assessment, documentation, and reporting of adaptive management can obscure successes. We outline a set of general principles for improving monitoring, evaluation, and adaptive management of environmental water regimes, and provide several examples from Australia and North America. Successful adaptive management depends upon the formation and maintenance of strong partnerships and an appreciation of the importance of individuals in teams. Through such partnerships, it is possible to coordinate monitoring programs over large scales, create programs of requisite simplicity, and use innovative approaches to evaluation. Finally, we note that although adaptive management has occurred in the past, too often it has been poorly documented and reported. The inclusion of reflectors in monitoring and evaluation teams will better capture the lessons learned by individual programs, improving adaptive management into the future.
Keywords: Environmental water management; Knowledge exchange; Legitimacy; implementation challenge

Adaptive management in wildlife conservation - Organ, John; Decker, D.J.; McDonald, J.E.; Riley, Shawn; Mahoney, S.P. (The Wildlife Society Techniques Manual, 2012)
Adaptive management in wildlife conservation emerged from the wildlife profession's search for better solutions to increasingly complex conservation challenges. Adaptive management is an effective process for wildlife managers to employ to (1) deal with uncertainty in the management system, (2) learn from their management actions, and (3) achieve desired results. Being adaptable or flexible in your management approach is not the same as managing adaptively or conducting adaptive management. Adaptive management requires adhering to a stepwise process and fully executing each step. A critical step is rigorous monitoring and assessment of management interventions. Without this, wildlife managers cannot achieve the essence of adaptive management, which is the explicit goal of learning more about the management system after each management action.

Participatory adaptive management leads to environmental learning outcomes extending beyond the sphere of science - Fujitani, Marie; McFall, Andrew; Randler, Christoph; Arlinghaus, Robert (Science Advances, 2017)
Resolving uncertainties in managed social-ecological systems requires adaptive experimentation at whole-ecosystem levels. However, whether participatory adaptive management fosters ecological understanding among stakeholders beyond the sphere of science is unknown. We experimentally involved members of German angling clubs (n = 181 in workshops, n = 2483 in total) engaged in self-governance of freshwater fisheries resources in a large-scale ecological experiment of active adaptive management of fish stocking, which constitutes a controversial management practice for biodiversity and ecosystem functioning when conducted inappropriately. The collaborative ecological experiments spanned several years and manipulated fish densities in 24 lakes with two species. In parallel, we experimentally compared changes in ecological knowledge and antecedents of proenvironmental behavior in stakeholders and managers who were members of a participatory adaptive management treatment group, with those receiving only a standard lecture, relative to placebo controls. Using a within-subjects pretest-posttest control design, changes in ecological knowledge, environmental beliefs, attitudes, norms, and behavioral intentions were evaluated. Participants in adaptive management retained more knowledge of ecological topics after a period of 8 months compared to those receiving a standard lecture, both relative to controls. Involvement in adaptive management was also the only treatment that altered personal norms and beliefs related to stocking. Critically, only the stakeholders who participated in adaptive management reduced their behavioral intentions to engage in fish stocking in the future. Adaptive management is essential for robust ecological knowledge, and we show that involving stakeholders in adaptive management experiments is a powerful tool to enhance ecological literacy and build environmental capacity to move toward sustainability. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders.

The Science in Adaptive Management - Ripley, Matt; Jaccard, Sabine (ILO, 2016)
‘Adaptive management’ is all the rage in international development circles. But to avoid yet another buzzword – we need to learn from the experience of natural resource science.
Keywords: IMPORTANT

Making Good Use of Adaptive Management - Doremus, Holly; Andreen, William L.; Camacho, Alejandro E.; Farber, Daniel A.; Glicksman, Robert L.; Goble, Dale D.; Karkkainen, Bradley C.; Rohlf, Dan; Tarlock, A. Dan; Zellmer, Sandra B.; Jones, Shana Campbell; Huang, Yee (White Paper #1104, 2011)

Adaptive Management in the Face of Climate Change and Endangered Species Protection - Gardner, Emily (Ecology Law Quarterly, 2013)

Uncertainty, Precaution, and Adaptive Management in Wildlife Trade - Wiersema, Annecoos (Michigan Journal of International Law, 2015)

Designing Monitoring and Evaluation Approaches for Learning An FOS How-To Guide - FOS (FOS, 2019)

Evidence to Action: Research to Address Illegal Wildlife Trade - Milner-Gulland, E. J.; Cugniere, Laure; Hinsley, Amy; Phelps, Jacob; Rolfe, Michael 't Sas; Veríssimo, Diogo (2018)
Tools and expertise to improve the evidence base for national and international Illegal Wildlife Trade policy already exist but are underutilised. Tapping into these resources would produce substantive benefits for wildlife conservation and associated sectors, enabling governments to better meet their obligations under the Sustainable Development Goals and international biodiversity conventions. This can be achieved through enhanced funding support for inter-sectoral research collaborations, engaging researchers in priority setting and programme design, increasing developing country research capacity and engaging researchers and community voices in policy processes. This briefing, addressed to policy makers and practitioners, is part of the 2018 Evidence to Action: Research to Address Illegal Wildlife Trade event programme, organised by five of the UK’s most active IWT research institutions, to support the London 2018 IWT Conference.

Emerging Technologies: Smarter ways to fight wildlife crime - Cressa, Douglas; Zommers, Zinta (Environmental Development, 2014)
The illegal trade of animals—for luxury goods, traditional medicine or cultural ceremonies, pets, entertainment, and even research—is a major threat to wildlife conservation and welfare (Baker et al., 2013). Poachers and illegal traders use highly sophisticated and rapidly changing techniques to avoid detection. To keep pace with the "war on wildlife", conservation and law enforcement communities have started to adopt cutting-edge military tools and techniques. High-tech equipment can magnify counter-poaching efforts without requiring armies of rangers or risking lives. Tools include acoustic traps, mobile technology, mikrokopters, radio frequency identification tags, encrypted data digital networks, camera traps, DNA testing, radio collars, metal scanners, and satellite imagery.